Extended relativistic multiconfiguration calculations of energy levels and transition properties in singly ionized tin. (January 2023) - Atalay, B.; Jönsson, P.; Brage, T.
Highlights: Atomic properties of singly ionized tin, excitation energies, wavelengths, oscillator strengths, lifetimes and transition rates, are systematically investigated. The MCDHF and RCI methods are employed. The contributions of valence-valence and core-valence correlation effects are studied in detail. The most accurate atomic data for singly ionized tin are provided. Abstract: Multiconfiguration Dirac-Hartree-Fock (MCDHF) and relativistic configuration interaction (RCI) calculations are performed for 22 states in singly ionized tin (Sn II) belonging to the 5 s 2 n s ( n = 6, 7 ), 5 s 2 n d ( n = 5, 6 ), 5 s 5 p 2 even parity configurations and the 5 s 2 n p ( n = 5, 6, 7 ), 5 s 2 4 f odd parity configurations. Valence-valence and core-valence correlation effects are taken into account through configuration state function (CSF) expansions. Complete and consistent data sets of level energies, wavelengths, oscillator strengths, lifetimes and transition rates among all these states are given. The results are compared with existing theoretical and experimental results. There is an excellent agreement for calculated excitation energies with experimental data from the NIST database. Lifetimes and transition rates are also in agreement with the results from previous calculations and available measurements for most of the transitions.